FEASIBILITY ANALYSIS OF HALF BEAD TECHNIQUE TO REPLACE POST-WELD HEAT TREATMENT IN WELDING A335 GRADE P22 PIPES - Haryadi, Haryadi; Arifin, Amir (Indonesian Journal of Engineering and Science, 2025)
This work evaluates the feasibility of using the Temper Bead Welding (TBW) method with the Half Bead technique as an alternative to Post-Weld Heat Treatment (PWHT) for welding A335 Grade P22 pipes. Three treatment methods were compared: preheating, preheating with TBW, and preheating with PWHT. Hardness testing is carried out using the Vickers microhardness testing method. The only preheat method showed the highest hardness values in the HAZ (342 HV), fusion zone (357 HV), and weld metal (334 HV). TBW with the half bead technique had higher hardness only in the base metal (191 HV). PWHT provides the most uniform hardness distribution, effectively relieves residual stresses, and homogenizes the microstructure. TBW reduced HAZ size by 50% more than preheating. The microstructure observed in all methods was ferrite and pearlite, with differences mainly in grain size. Although TBW is a viable alternative for repair, this method is unsuitable for application in early fabrication processes.